(untitled) (LACCEI, 2024)
Project management through scope management based on the Work Breakdown Structure tool, WBS, offers the possibility of improving project management indicators, pointing directly to the achievement of value for organizations. This investigation was able to identify that overconfidence and ignorance of the fundamental tools and techniques of project management is one of the reasons that directly and negatively impacts the scope, schedule and cost of electrical projects in the industrial sector. Additionally, it delivers an agile guide and EDT type that seeks to promote the use of basic tools and at the same time improve results.